Entrance Surface Dose in Intravenous Pyelography Patients at Songklanagarin Hospital - Krisanachinda, Anchali; Sakjirapapong, Seri; Viriyabubpha, Thamanoon; Funsian, Amporn (The ASEAN Journal of Radiology, 2023)
The purposes of the study are to determine of entrance surface dose and the dose reference level from Intravenous Pyelography patients during April-July 2008 at Songklanagarind Hospital. The doses were calculated at the patient skin from 121 patients in 7 radiographic routine projections: scout IVP AP view, 5 min after contrast media injection, 10 min prone, 10 min supine, 30 min, full bladder and post voiding. The results showed the mean /third quartile entrance skin doses, using as the dose reference level at this center, for the 7 projections of 1.90/2.10, 2.93/3.47, 1.72/2.00, 2.22/2.68, 2.39/2.76. 2.99/3.44 and 2.25/2.70 mGy respectively. Most of the dose levels were generally within normal range of the diagnostic reference levels specified by European Commission as the European Guidelines for KUB studies of 10 mGy for entrance surface dose of a standard sized patient. However, there was one record with over normal range value caused by improper radiographic exposure technique.